Teacher Induction: Exploring Beginning Teacher Mentorship - Hellsten, Laurie‐ann; Prytula, Michelle; Ebanks, Althea; Lai, Hollis (Canadian Journal of Education/Revue canadienne de l'éducation, 2010)
Induction programs, including mentorship, serve to bridge the transition from pre‐ service to in‐service teaching. This study explored the mentorship experiences of Saskatchewan beginning teachers. Analysis of interviews identified three themes: assigned/unassigned mentors, engaged/disengaged mentors, and single/multiple mentors. One moderating theme also emerged: the compatibility of the mentor and beginning teacher. The combination of themes provides preliminary support for an alternative model of mentoring based on learning communities and founded on the concepts of strong and weak ties and the constructivist model of knowledge. Key Words: theoretical model, mentor relationship, multiple mentors, learning com‐ munities Les programmes d’insertion professionnelle, dont les programmes de mentorat, ser‐ vent à faciliter la transition entre la formation initiale à l’enseignement et la prati‐ qued’enseignement. Cette recherche porte sur les expériences de nouveaux ensei‐ gnants en Saskatchewan. L’analyse des entrevues effectuées a permis d’identifier trois thèmes : mentors attitrés/non attitrés, mentors actifs/peu impliqués et mentor unique/mentors multiples. Un autre thème entre également en ligne de compte : la compatibilité entre le mentor et le nouvel enseignant. La combinaison de ces thèmes fournit un cadre préliminaire pour un nouveau modèle de mentorat axé sur des communautés d’apprentissage et fondé sur les concepts de liens étroits et faibles et le modèle constructiviste du savoir. Mots clés : modèle théorique, relation au mentor, mentors multiples, communautés d’apprentissage